2010
DOI: 10.1080/08941920903357782
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Perceptions of Rural South African Residents: The Complex Nature of Environmental Concern

Abstract: The state of the local environment shapes the well-being of millions of rural residents in developing nations. Still, we know little of these individuals' environmental perceptions. This study analyzes survey data collected in an impoverished, rural region in northeast South Africa, to understand the factors that shape concern with local environmental issues. We use the "post-materialist thesis" to explore the different explanations for environmental concern in less developed regions of the world, with results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Access to education programs and environmental discourse has been demonstrated as an important determinant in environmental perception (Hunter et al 2007). Males and those classified as well off (not exclusively males) reported more ecosystem services from the wetlands.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Access to education programs and environmental discourse has been demonstrated as an important determinant in environmental perception (Hunter et al 2007). Males and those classified as well off (not exclusively males) reported more ecosystem services from the wetlands.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…However, this evaluation references the OPSV hypothesis as a whole, whereas the objective problem part is largely considered to be valid, even by critics such as Brechin (1999). Moreover, recent research has confirmed the existence of the postulated negative association between local environmental conditions and concern (Hunter, Strife, and Twine, 2010). However, Dunlap and York (2008, p. 537) caution that even the straight-forward effect of objective problems on environmental concern is not a simple “stimulus-response phenomenon.” Rather, the multifaceted influence of media, science, government agencies, education, and environmental organizations mediates the relationship (e.g., Frank, 1997; Frank et al, 1999).…”
Section: Conceptual Framing and Literature Reviewmentioning
confidence: 85%
“…For instance, research on single countries explored advanced industrial countries like the United States (Dunlap et al 2000;Klineberg, McKeever, and Rothenbach 1998;Van Liere and Dunlap 1981), Canada (Edgell and Nowell, 1989), Britain (Clements 2012;Norris 1997), Israel (Drori and Yuchtman-Yaar 2002), Sweden (Gooch 1995;Widegren 1998), Norway (Olli, Grenstad, and Wollebaek 2001), and Australia (McAllister 1994;Tranter 2012). A few studies considered developing countries and emerging economies in other geographic regions, including Korea (Kim 1999), Turkey (Furman 1998;Goksen, Adaman, and Zenginobuz 2002), Ghana (White and Hunter 2009), South Africa (Hunter, Strife, and Twine 2010), and, recently, Brazil (Aklin et al 2013) and China (Shields and Zeng 2012;Xiao, Dunlap, and Hong 2012;Hong 2010, 2012).…”
Section: Research On Environmental Concern: Single-country Comparatimentioning
confidence: 95%